Hubungan Indeks Masa Tubuh pada Balita Stunting Terhadap Kadar Hemoglobin di Kecamatan Gunung Sugih Kabupaten Lampung Tengah - Frigandra Syahputri; Khairun Nisa Berawi; Eca Cania (CV. Jasa Sukses Abadi, 2020)
The prevalence of stunting in Gunung Sugih District, Lampung Tengah Regency, Lampung Province is high for stunting category in Indonesia. Nutritional status in stunting can be measured by body mass index according to age (BMI /A). Stunting has anemia as hemodynamic problems due to lack of iron (Fe) intake. The parameter which is used for measure anemia is hemoglobin. This study aims to determine the relationship between BMI in stunting children and hemoglobin levels as a marker of anemia. Observational analytic method with cross sectional approach was used in this study with 35 samples (cluster random sampling). Primary data are height, weight, body mass index (BMI) and hemoglobin (Hb) levels as measured by Hb Meter (Dr.Family®). Data analysis was performed by Pearson correlation test. Obtained a normal BMI of -0.51SD with a percentage of 94.3%. Hb levels with a mean of 10.4 g/dL and 57.1% of children had anemia. The results of the Pearson correlation test found that Ho was received with value of p=0.511 (p>0.05) and had a positive correlation (r=0.115). This study did not show a significant relationship between body mass index (BMI) of hemoglobin (Hb) levels as a marker of anemia in stunting infants in Gunung Sugih District, Central Lampung Regency.